(untitled) (VERITAS LEGIS JOURNAL, 2026)
The author, the former Chairman of the Constitutional Court of the Republic of Kazakhstan, a prominent statesman of the Republic of Kazakhstan, examines the process of dividing legal regulation into separate, specialized areas, which is relevant for the theory of domestic law, determined by the development and diversity of social relations, the integration of legal systems and special branches of law. The fragmentation of law is objectively determined by the instability of legislation, the inconsistency and lack of coordination of legislative activity at its various stages, and the trend towards strengthening the processes of implementation and reception of law. And as a consequence, the weakening of the systemic structure of law, conflicting legal provisions, difficulties for law enforcement officers, and the potential threat of loss of structuring of the legal system and the legal system.